Parameter Adaptation Algorithms - Landau, Ioan Doré; Constantinescu, Aurelian; Airimițoaie, Tudor-Bogdan; Castellanos-Silva, Abraham (Adaptive and Robust Active Vibration Control, 2017)
Parameter adaptation algorithms are the key step for estimating the parameters of the discrete time dynamic model of the system to be controlled and for building an adaptive active vibration control system. A coverage of the subject is provided from the perspective of the user. Stability and convergence issues are addressed.